Role of reinsurance in Natural Catastrophes - Kataev, Egor (2018)
This work examines what such reinsurance is and why such firms and corporations areneeded, as well as their role in large natural disasters. We will consider what reinsuranceis inherently, what types of reinsurance and contracts exist, we will also consider whatare natural disasters and their various types, and also what natural disasters are affectedby the three main regions, America, Asia and Europe. The main purpose of this work willbe to understand why the scope of reinsurance is more risky than insurance. Consider, asan example, one of the biggest incidents of Hurricane Katrina, which affected the wholeinsurance industry.